The phosphatidylcholine-hydrolysing phospholipase C NPC4 plays a role in response of Arabidopsis roots to salt stress - Kocourková, Daniela; Krcková, Zuzana; Pejchar, Premysl; Veselková, Stepánka; Valentová, Olga; Wimalasekera, Rinukshi; Scherer, Günther F E; Martinec, Jan (Journal of experimental botany, 2011)
Phosphatidylcholine-hydrolysing phospholipase C, also known as non-specific phospholipase C (NPC), is a new member of the plant phospholipase family that reacts to environmental stresses such as phosphate deficiency and aluminium toxicity, and has a role in root development and brassinolide signalling. Expression of NPC4, one of the six NPC genes in Arabidopsis, was highly induced by NaCl. Maximum expression was observed from 3 h to 6 h after the salt treatment and was dependent on salt concentration. Results of histochemical analysis of P(NPC4):GUS plants showed the localization of salt-induced expression in root tips. On the biochemical level, increased NPC enzyme activity, indicated by accumulation of diacylglycerol, was observed as early as after 30 min of salt treatment of Arabidopsis seedlings. Phenotype analysis of NPC4 knockout plants showed increased sensitivity to salinity as compared with wild-type plants. Under salt stress npc4 plants had shorter roots, lower fresh weight, and reduced seed germination. Expression levels of abscisic acid-related genes ABI1, ABI2, RAB18, PP2CA, and SOT12 were substantially reduced in salt-treated npc4 plants. These observations demonstrate a role for NPC4 in the response of Arabidopsis to salt stress.
Keywords: signální transdukce; Signal Transduction; proteiny huseníčku; geneticky modifikované rostliny; chlorid sodný; polymerázová řetězová reakce s reverzní transkripcí; Type C Phospholipases; Arabidopsis Proteins; fosfolipasy typu C; Reverse Transcriptase Polymerase Chain Reaction; regulace genové exprese u rostlin; Gene Expression Regulation, Plant; Arabidopsis; Abscisic Acid; kořeny rostlin; Plants, Genetically Modified; Sodium Chloride; kyselina abscisová; Plant Roots